2020
DOI: 10.1002/adom.202000414
|View full text |Cite
|
Sign up to set email alerts
|

Organic Light‐Emitting Diodes Based on a Columnar Liquid‐Crystalline Perylene Emitter

Abstract: Liquid crystalline materials possess great potential as emitters in organic light‐emitting diodes (OLEDs) due to their self‐assembling property, which may lead to anisotropic films and improved charge transport. Here, the key photophysical properties of the columnar liquid crystalline emitter perylene‐3,4,9,10‐tetracarboxylic tetraethyl ester (PTCTE) are investigated and the material is implemented into OLEDs. It is found that vacuum‐deposited PTCTE films exhibit preferential horizontal orientation of the tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…The figure was made using data from 53 separate reports that include EQE max and emitter orientation data on 124 materials systems. [ 20,22–24,37–85 ] While there is no correlation between EQE max and anisotropy across all data, it is clear that the highest efficiency in TADF‐ and non‐TADF‐based systems, respectively, is reached at low anisotropy factors.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…The figure was made using data from 53 separate reports that include EQE max and emitter orientation data on 124 materials systems. [ 20,22–24,37–85 ] While there is no correlation between EQE max and anisotropy across all data, it is clear that the highest efficiency in TADF‐ and non‐TADF‐based systems, respectively, is reached at low anisotropy factors.…”
Section: Introductionmentioning
confidence: 92%
“…Mater. 2021, 33, 2100677 [38,41,42,52,56,61,[67][68][69]74,93,110,112] The color coding corresponds to the color of the symbols plotted in Figure 10.…”
Section: Neat Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…further investigated the TDM orientation of the LC emitter perylene-3,4,9,10-tetracarboxylic tetraethyl ester (PTCTE), when doped in different host materials. 21 The TDM of PTCTE shows preferential horizontal orientation (72% horizontal) as a 2 wt% doped TCTA:TPBi film but with a low FPL of 14%; however, the orientation is isotropic in a TCTA:B3PYMPM film (FPL of 13%). 21 As a result, the OLEDs based on PTCTE/TCTA:B3PYMPM exhibited very low EQEmax below 0.3% at λEL of 550 nm, while for device based on PTCTE/TCTA:TPBi showed an improved EQEmax of 0.8% at λEL of 580 nm.…”
Section: Introductionmentioning
confidence: 93%
“…19 It is possible to infer the average orientation of the TDMs within a film, 4 which is done typically by either angle-resolved photoluminescence (ARPL) or variable-angle spectroscopic ellipsometry (VASE) studies. [19][20][21] Yokoyama's fundamental work on small molecule orientation in vacuum-deposited films has demonstrated that to minimize the surface energy, the ''first'' layer of the molecules deposited on the interface adopts a horizontal orientation, but then the molecules can quickly undergo surface diffusion until the orientation is fixed by successively overlaying molecules. 2 Indeed, the orientation of the TDM in vacuum-deposited films is influenced by not only the intrinsic anisotropy of the emitter molecule, 22 but also the temperature of the substrate, 23 and the intermolecular interactions within the emissive layer.…”
Section: Introductionmentioning
confidence: 99%